West Sumatra local chili genotype appearance test - Ediwirman, Ediwirman; Salfiati, Salfiati; Putra, Oktaviandra (Jurnal Agrotek Ummat, 2023)
Chilli is an economically valuable horticultural crops.  The exploration of local chilli genetic resources is expected to provide qualitative and quantitative character information.   The study aimed to test the appearance of local chilli genotypes in West Sumatra based on qualitative and quantitative characters.   The research was conducted on dry land in Tiaka Village, East Payakumbuh Subdistrict, Payakumbuh City, West Sumatra Province at an altitude of 515 m above sea level.  The research was carried out from December 2020 to August 2021.   The research used a fully randomised complete group design (RKLT) with 4 Treatmen 6  replications.  The chilli genotypes tested were; Aka, Keriting Bukittinggi, Gero and Kopay.  Variable observation of qualitative characters consisted of; anthocyanin staining on hypocotyl, stem colour, stem cross-sectional shape, leaf shape, leaf colour, flower shape, flower petal colour, flower crown colour, stigma colour, young fruit colour, old fruit colour, fruit shape, seed shape and seed colour.  Quantitative traits were: plant height, stem diameter, flowering age, harvest age, fruit length, fruit diameter, number of fruits per plant, fruit weight, fruit weight per plant, fruit weight per plot, fruit weight per ha. Data for quantitative characters were analysed using PKBT-STAT 3.1C statistical software.  Data for the quantitative characters leaf length, leaf width and 1000 seed weight were not statistically analysed.  The results of the study concluded that Aka is one of the candidates for superior varieties.  Aka chilli produces a lot of fruit (166.27 fruits/plant) with fruit weight reaching 26.95 tons/ha heavier than the Kopay variety as a comparison with fruit weight reaching 22.60 tons/ha.